Special Economic Zones (SEZ): Challenges and Opportunities in Nepal (Research Nepal Journal of Development Studies, 2020)
The Special Economic Zone (SEZ) is that specific geographical area which has economic and other business laws that are more market-oriented than a country’s typical or national laws. It is the region where government provides the special facilities by constructing separate rules and regulations and wants to promote foreign investments and capital for export oriented economy. National laws may be suspended inside a special economic zone. This article describes the different aspects of SEZ in global and national context, policies and present situations of SEZ in Nepal. The overall objective of this article is to find out the present situation of special economic zones of Nepal. The specific objective is to analyze the overall conditions of SEZ, their challenges and opportunities in Nepal. the analytical and descriptive methods are applied in this study. The data used in the study is quantitative which are collected from the economic survey of the ministry of finance, ministry of industry, commerce and supply, World Bank, OECD, SEZ office, published articles and newspapers related to SEZ and reports. In conclusion, to achieve high speed of economic development, to generate employment opportunities and to increase direct foreign investment are the main goals of SEZ. The government of Nepal has implemented formally the concept of Special Economic Zone in 2000 AD and constructed laws, act and policies and implemented after 2017 A D.